MOVING AVERAGE CONTROL CHART FOR MONITORING PROCESS MEAN IN INAR(1) PROCESS WITH ZERO INFLATED POISSON - Areepong, Yupaporn (MATTER: International Journal of Science and Technology, 2018)
In this paper, the explicit formulas are proposed to evaluate the Average Run Length (ARL) of the Moving Average control chart (MA) for the first order integer-valued autoregressive with Zero Inflated Poisson mode (ZIPINAR(1)). The performance of MA and Exponentially Weighted Moving Average (EWMA) charts are compared. The results shown that, for the performance of MA chart is superior to EWMA chart. Especially, for upward shifts the performance of the MA chart gets better when the value of the span () decreases. However, for EWMA performs better than MA chart for all magnitudes of changes.